Ranking - A Useful Tool for University Governance - Vũ, Anh Thị Mai; Nguyễn, Chung Hữu Thành; Nguyễn, Thanh Quý; Nguyễn, Đức Hữu (VNU Journal of Science: Social Sciences and Humanities; Vol 31 No 4, 2015)
Innovative management of higher education in Vietnam is supposed to be connected with the mission and strategic governance. Practically, it is realized through the management of core indicators concerning the education, research quality and the internationalized level.  In this case, the participation in the international university ranking leagues not only helps contribute to the world higher education integration but also the university benchmark. However, this should be performed in terms of the university mission. This paper focuses on the determinants of quality, quality measurement and relationships between mission and quality, quality and ranking, ranking and mission. In particular, in the epode of information society, innovative management is efficiently supported by bibliometrics analysis. Vietnam National University, Hanoi can be considered as a case study for this approach. Keywords: Quality, mission, ranking, bibliometrics